2000
DOI: 10.4049/jimmunol.164.3.1346
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Liver-Derived Dendritic Cell Progenitors on Th1- and Th2-Like Cytokine Responses In Vitro and In Vivo

Abstract: There is evidence that donor-derived dendritic cells (DC), particularly those at a precursor/immature stage, may play a role in the immune privilege of liver allografts. Underlying mechanisms are poorly understood. We have examined the influence of in vitro generated mouse liver-derived DC progenitors (DCp) on proliferative, cytotoxic, and Th1/Th2 cytokine responses induced in allogeneic T cells. Liver DCp, propagated in GM-CSF from C57B10 mice (H2b), induced only minimal proliferation, and weak cytotoxic resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
114
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(122 citation statements)
references
References 77 publications
(76 reference statements)
7
114
0
1
Order By: Relevance
“…In fact, these potentially "tolerogenic" events (increase in IL-10 and decrease in IFN-␥ gene transcription) occur in primary MLC culture in presence of LDC isolated from partially hepatectomized animals. According to these data, several authors show that immature DC can induce the development of T cell hyporesponsiveness or T regulatory cells that can promote tolerance, [34][35][36] a finding in keeping with the polarization toward Th2 cytokine production by LDC observed in the current study. SDC isolated at the same time as LDC did not show such changes in their IL-10 and IFN-␥ gene transcription or in their ability to modulate cytokine production by naïve T-cells.…”
Section: Discussionsupporting
confidence: 87%
“…In fact, these potentially "tolerogenic" events (increase in IL-10 and decrease in IFN-␥ gene transcription) occur in primary MLC culture in presence of LDC isolated from partially hepatectomized animals. According to these data, several authors show that immature DC can induce the development of T cell hyporesponsiveness or T regulatory cells that can promote tolerance, [34][35][36] a finding in keeping with the polarization toward Th2 cytokine production by LDC observed in the current study. SDC isolated at the same time as LDC did not show such changes in their IL-10 and IFN-␥ gene transcription or in their ability to modulate cytokine production by naïve T-cells.…”
Section: Discussionsupporting
confidence: 87%
“…Another possible explanation for suppressed MLR in siRNA-IL12p35-transfected DC is that the increased IL-10 production may act as an inhibitor of T cell proliferation (37,38). Other studies examining naturally occurring Th2-promoting DC have shown that these cells have a reduced allostimulatory function and reduced IL-12 production (39,40). The combination of Th2-promoting properties as well as poor allostimulation suggests that siRNA-IL12p35-transfected DC may possess the phenotype of a "tolerogenic" DC and thus may be useful for treatment of Th1-mediated autoimmune diseases and transplant rejection.…”
Section: Discussionmentioning
confidence: 99%
“…First, these regulatory T cells may be generated in situ in the liver by antigenic activation by hepatic APC. In fact, hepatic sinusoidal endothelial cells and dendritic cells can present Ags (3,4,35). Alternatively, these regulatory T cells can develop in GALT (14) and then migrate to the liver.…”
Section: Discussionmentioning
confidence: 99%